THE RELATIONS OF THE SCIENCE OF LAW WITH THE SOCIAL SCIENCES - Monge, Daniel Camacho (2022)
A topic that provokes discussions, sometimes spirited, is that of the relations between the Science of Law and the Social Sciences.